Structural templates of disordered granular media. (February 2015) - Walker, David M.; Tordesillas, Antoinette; Zhang, Jie; Behringer, Robert P.; Andò, Edward; Viggiani, Gioacchino; Druckrey, Andrew; Alshibli, Khalid
Abstract: Granular materials, in common with many complex systems, exhibit a range of self-organization processes that control their mechanical performance. Many of these processes directly manifest in the evolution of the contact network as the material responds to applied stresses and strains. Yet the connections between the topology, structure and dynamics of this evolving contact network remain poorly understood. Here we demonstrate that dense granular systems under a variety of loading conditions exhibit preferred structural ordering reminiscent of a superfamily classification. In particular, two distinct superfamilies are discovered: the first is typically exhibited by materials in the pre-failure regime, while the second manifests in the unstable or failure regime. We demonstrate the robustness of these findings with respect to a range of packing fractions in experimental sand and photoelastic disk assemblies subject to compression and shear, as well as in a series of discrete element simulations of compression tests. We show that the superfamily classification of small connected subgraphs in a granular material can be used to map boundaries in a so-called jamming phase diagram and, consequently, offers a key opportunity to bridge the mechanics and physics perspectives on the constitutive behavior of granular systems.